3-Dimensional JEG-3 choriocarcinoma cell organoids as a model for trophoblast expansion and differentiation. (15th January 2021) - Dietrich, B.; Kunihs, V.; Haider, S.; Pollheimer, J.; Knöfler, M.
Abstract: JEG-3 choriocarcinoma cells have been widely used as a model for placental trophoblast. Herein, 3-dimensional (3D) JEG-3 organoids (JEG-3-ORGs) were established using a protocol that we recently developed for primary cytotrophoblast organoids (CTB-ORGs). 3D JEG-3-ORGs, cultivated in basic culture medium, rapidly divide and spontaneously undergo differentiation. Under stem cell culture conditions (activation of WNT/EGF signalling and inhibition of TGF-β signalling) smaller organoids with reduced proliferative capacity were generated specifically abolishing expression of extravillous trophoblast (EVT)-specific genes. Similar to CTB-ORGs, removal of the WNT activator CHIR99021 induced re-expression of these genes in JEG-3-ORGs. Hence, JEG-3-ORGs could be used as a model for directed EVT differentiation. Highlights: Establishment of 3-dimensional organoids from JEG-3 choriocarcinoma cells. JEG-3 organoids, propagated in basic culture medium, show high rates of proliferation and spontaneous differentiation. Cultivation of JEG-3 organoids under stemness culture conditions suppresses extravillous trophoblast-specific genes. Removal of the WNT activator CHIR99021 from the stem cell medium induces formation of HLA-G-expressing cells.